The photographic atlas of Spanish food consistency: A new tool for the treatment of dysphagia - Ruiz Brunner, María de Las Mercedes (2019)
Dysphagia requires texture-modified foods and thickened liquids, which is difficult to explain to patients and caregivers. Methods: an atlas has been developed and validated to explain the consistencies using the Likert scale questionnaire and the Delphi survey. The agreement and reliability of the tool were evaluated, with a minimum of 80%. The atlas was developed in Spanish. Results: an agreement of 93.3% (95% CI: 63.7-100%) was obtained during the evaluation and a value of 97.5% and a Kappa index of 0.96 (95% CI: 0.93-0.99; p = 0.016] were obtained during the validation processes. Conclusion: the atlas is a new valid tool that can be used by health professionals.